frizzled and frizzled 2 play a partially redundant role in wingless signaling and have similar requirements to wingless in neurogenesis. - Bhat, K.M. (Cell, 1998)
The Drosophila Frizzled (Fz) and Frizzled2 (DFz2) proteins function as receptors for Wingless (Wg) in tissue culture cells. While previous results indicate that loss of function for fz has tissue polarity defects, loss-of-function effects of Dfz2 are not known. Here, we have examined the requirements of fz and Dfz2 during neurogenesis. Our results indicate that both Fz and DFz2 function in Wg signaling, and loss of either of the two affects the same subset of neuroblasts as those affected by loss of wg. While these defects are partially penetrant in embryos lacking either fz or Dfz2, the penetrance is significantly enhanced in embryos lacking both. Since the penetrance of the CNS phenotypes is not complete in double mutants, additional components that allow some degree of Wg signaling must exist in vivo.